Peace in Waziristan: Success or setback in the fight against terrorism in Afghanistan and Pakistan? - Christian Wagner; Citha Doris Maaß (Stiftung Wissenschaft und Politik (SWP), 2006)
At a remarkable dinner for three that took place in Washington on 27 September 2006, President Bush, backed by the Afghan president, Hamid Karzai, once again urged Pakistan's president Pervez Musharraf to take tougher action against terrorist bases in the border regions of Pakistan. However, Musharraf's options are limited as he faces increasing domestic opposition because of his close cooperation with the USA in the fight against terrorism. This limitation is illustrated by the agreement of Miranshah, which was signed on 5 September 2006 by the governor of Pakistan's North West Frontier Province (NWFP) and the tribes of North Waziristan in the Federally Administered Tribal Areas (FATA). Foreign terrorists and neo-Taliban groups have for years been using this region as a retreat and a base for infiltrating Afghanistan to fight the government of President Karzai and the international troops. Since the start of the military campaign in South Waziristan in spring of 2004, the Pakistani army has not succeeded in controlling the tribal groups, stopping the neo-Taliban infiltration of Afghanistan, or integrating the FATA into the Pakistani state. While the agreement may bring about a cessation of hostilities in North Waziristan, it could constitute a setback to the battle against terrorism in Afghanistan and Pakistan.(SWP Comments / SWP)
Keywords: 320